2017
DOI: 10.5812/jjcdc.62315
|View full text |Cite
|
Sign up to set email alerts
|

Massage for Pain Management in Patients with Sickle Cell Disease: A Review Study

Abstract: Context: The most common side effect reported by Sickle cell disease patients is unforeseen and chronic pain crisis. A combination of pharmacological and non-drug treatments is suggested for managing pain in patients with SCD. One of the non-drug treatments is massage therapy. This study aimed to evaluate the use and effectiveness of massage in reducing pain in patients with SCD.Evidence Acquisition: This study is a literature review of the period of 1990 to 2016. The search was done in databases and reputable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…10 A review of five RCTs found that MT can provide significant pain reduction; improve functional status; reduce depression, anxiety, and stress; and potentially reduce analgesic use and length of stay. 11 Given the significant pain burden, 12 severity of vaso-occlusive crises, 13 barriers to accessing nonpharmacologic pain management, 14 and structural racism 15…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 A review of five RCTs found that MT can provide significant pain reduction; improve functional status; reduce depression, anxiety, and stress; and potentially reduce analgesic use and length of stay. 11 Given the significant pain burden, 12 severity of vaso-occlusive crises, 13 barriers to accessing nonpharmacologic pain management, 14 and structural racism 15…”
Section: Introductionmentioning
confidence: 99%
“…Even fewer studies have examined MT among children and adolescents with SCD, despite these individuals often being hospitalized within the same medical oncology units as children and adolescents with cancer 10 . A review of five RCTs found that MT can provide significant pain reduction; improve functional status; reduce depression, anxiety, and stress; and potentially reduce analgesic use and length of stay 11 . Given the significant pain burden, 12 severity of vaso‐occlusive crises, 13 barriers to accessing nonpharmacologic pain management, 14 and structural racism 15 affecting individuals with SCD, research is needed to understand the effectiveness of MT within this population as distinct from patients with other hematologic and/or oncologic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…This finding also puts to question the additional benefits of some forms of CAM, particularly massage whose beneficial effects evaluated by previous studies were conflicting, probably due to application by patients and relatives who are mostly non-professionals. 30 Moreover, the long term efficacy of CAM cannot be reflected in our findings given the study period.…”
Section: Articlementioning
confidence: 67%
“…3 IHM modalities involve the coordinated combination of conventional medicine (e.g., medication, physical rehabilitation, and surgery) and evidence-based modalities such as acupuncture, music therapy, massage, and chiropractic care to address the needs of the whole person (body, mind, and spirit). 6 Several clinical trials have supported the benefits of IHM modalities including acupuncture 7 and massage therapy 8 for addressing acute pain among youth and adults with SCD, and music therapy for addressing acute 9 and chronic pain 10 among adults with SCD. Additionally, recent observational studies have demonstrated the clinical effectiveness of massage therapy 11 and music therapy 12 among pediatric and adult patients with SCD, respectively.…”
Section: Introductionmentioning
confidence: 99%